Diagnosis approach, treatment, evaluation and fertility preservation in patient with Herlyn-Werner-Wunderlich syndrome: a case report - Indraswari, Lathifa Nadhya; Pangastuti, Nuring; Dwi Saputra, Akbar Novan; Widyasari, Anis (Universitas Gadjah Mada, 2023)
Herlyn-Werner-Wunderlich (HWW) syndrome is a very rare female congenital anomaly of urogenital tract. The definite etiology of HWW syndrome is still unknown. It may be caused by the abnormal development of Mullerian and Wolffian ducts. The characteristic triad of this syndrome includes didelphys uterus, obstructed hemivagina, and ipsilateral renal agenesis, recently known as Obstructed Hemivagina and Ipsilateral Renal Anomaly (OHVIRA) syndrome. A 17 y.o. presented with intermittent lower abdominal pain. Physical examination revealed in normal limit. From the ultrasonography examination, it was found uterus didelphys with left hemiuterus hematomethra, hematocolpos, with normal anatomy and function of the right kidney, but there was no left kidney. From pelvic magnetic resonance imaging (MRI) and laparoscopy showing a complete duplication of the uterus from the horn to the cervix with no connection between the two uterine cavities. Both ovaries were normal. The right fallopian tube was normal. The left tube was enlarged, attached to the uterus and the left ovary. No left kidney was found. From the previous surgery, there was a misdiagnosed with brown cyst. Physical examination such as rectal toucher often missed, regardless it can be used to determine some differential diagnosis. MRI is most accurate for providing details regarding the altered anatomy and for identifying associated hematocolpos, hematosalping or hematometra for HWW syndrome cases. The laparoscopy guiding diagnostic and operative management of the vaginal septectomy procedure was performed. In conclusion, misdiagnosis of HWW syndrome can be occurred on ultrasound examination. MRI is an examination that is considered appropriate to help confirm the diagnosis. Laparoscopy can be used with the aim of establishing a diagnosis or in surgical management, in this case, a septectomy is performed.